Nasal polyp fibroblasts (NPFs)-derived exosomes are important for the release of vascular endothelial growth factor from cocultured eosinophils and NPFs. Issue 3 (June 2022) - Shimizu, Shino; Tojima, Ichiro; Nakamura, Keigo; Arai, Hiroyuki; Kouzaki, Hideaki; Shimizu, Takeshi
Abstract: Objective: Significant eosinophil infiltration and tissue remodeling are common characteristics of conditions associated with chronic airway inflammation, such as chronic rhinosinusitis with nasal polyp and bronchial asthma. This study was designed to elucidate the role of eosinophil-fibroblast interactions in tissue remodeling during chronic airway inflammation. Methods: Peripheral blood eosinophils or EoL-1 eosinophilic leukemia cells were cocultured with nasal polyp fibroblasts (NPFs). Coculture-induced release of exosomes, major components of extracellular vesicles (EVs), and a profibrotic cytokine, vascular endothelial growth factor (VEGF), were evaluated by enzyme-linked immunosorbent assay. Results: Eosinophil-NPF interactions stimulated the release of exosomes and VEGF into culture supernatants. Coculture-induced release of exosomes was stimulated earlier than VEGF release, at 3 h of incubation. The average size of the EVs released by NPFs was 133 ± 3.6 nm. NPF-derived EVs (exosome concentration: 25 pg/mL) significantly stimulated VEGF release from EoL-1 cells. Pretreatment of NPFs with exosome inhibitor, GW4869 or DMA attenuated the release of exosomes and VEGF from cocultured EoL-1 cells and NPFs. Conclusion: The results of this study indicate that eosinophil-fibroblast interactions are important in the pathophysiology of tissue remodeling in eosinophil-predominant airway inflammation and that NPF-derived exosomes play a crucial role in the release of VEGF.